Peningkatan Kinerja Organisasi Sebagai Upaya Pengembangan Desa Wisata Seni dan Budaya Sendangasri Kabupaten Rembang - Tahwin, Muhammad; Liana Dewi, Dian Ayu; Sodiq, Fajar (Fokus ABDIMAS, 2023)
Sendangasri Village is included in the 28 tourist villages designated by the Rembang Regency government as Arts and Culture Tourism Villages. The results of the Community Service Team's observations at the Sendangasri Tourism Village succeeded in identifying that unprofessional management resulted in the Sendangasri Tourism Village still rarely being visited by tourists. This management problem is also supported by the fact that most managers have their own busy schedules, so managing tourist villages optimally is still not possible. The solution offered is to optimize the functions and roles of tourism village managers through motivational and management training. This service activity is carried out through several methods to solve problems, namely observation, training and mentoring. The results of the service carried out in Sendangasri Village are (1) There has been an increase in the performance of tourism managers, (2) There has been an increase in the tourism management capabilities of tourism village managers. Keywords: Training, Assistance, Performance, Development, Tourism Village